Performance And Precision Evaluation Of Multidimensional Databases - Ong Wai Kit, Janson Luke (2010)
Explosion of information in the business environment demands acquisition of reliable data warehouse and suitable information extraction technology. Data warehouse in combination with Online Analytical Processing (OLAP) multidimensional database (MDDB) has become the de-facto for decision support systems.